Aprendizaje cooperativo como estrategia didáctica para la resolución de ecuaciones en estudiantes de Educación General Básica - Macas Cuenca, Luis Enrique (2024)
The research work refers to Cooperative Learning as a didactic strategy, which encourages active and autonomous participation in the construction of knowledge of students in the process of teaching equations, because it promotes both individual and group learning. Therefore, the objective was to determine the importance of Cooperative Learning as a methodological strategy in the process of teaching equations in EGB-S students. It was used a qualitative approach of descriptive type with documentary design, the indexing technique was applied to collect the most relevant information, obtaining as a result that Cooperative Learning as a methodological strategy allows achieving a teaching-learning process where the student becomes the main protagonist by encouraging active, autonomous participation and the integral development of the students, so it is concluded that Cooperative Learning stands out for being an integral and effective strategy to teach equations in EGB-S students. Keywords: Cooperative learning, Didactic strategy, Methodological strategy, Teaching and learning.